Syntax Formation in Brahui Folklore and Usage of Personal Pronouns - Sani, Liaquat Ali; Ahmed, Muneer; Rasool, Zahida Ghulam (Makhz (Research Journal), 2023)
Brahui, a language spoken in the Balochistan region of Pakistan, is known for its rich and vibrant tradition that has been passed down through generations, particularly in the form of "Brahui Lok Shaeri" or Brahui folk poetry. This poetic genre has gained popularity over the year’s one of the defining characteristics of Brahui folk poetry is its unique sentence structure and linguistic features that set it apart from conventional literary languages, offering an insightful glimpse into the culture and language of the Baloch people. However, there exist certain intriguing variations within the Brahui Loc poetry, like other languages, exhibits various dialectal differences, including variations in personal pronoun usage. This research paper explores the substitution of personal pronoun cases in Brahui folklore, with a specific focus on the Jhalavani dialect. Notably, we delve into the unique phenomenon where the genitive pronoun "Na" (’you’) is replaced with the dative-accusative pronoun "ne" in the Jhalavani dialect, a feature not found in other Brahui dialects. Particularly concerning sentence structure and the use of pronouns. In this research article, we delve into the formation of spontaneous verses in Brahui folk poetry, with a particular focus on two distinct changes that occur in the formation of sentences: the alteration in sentence structure and the use of personal pronouns. These variations and provide an in-depth analysis of how they affect the structure and nuances of Brahui poetry.